Variasi Waktu Elektrolisis Menggunakan Elektroda Alumunium untuk Menurunkan COD Limbah "Batik Ayu" di Pijenan, Wijirejo, Pandak, Bantul - Mia Nandha Sari; Tuntas Bagyono; Choirul Amri (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
The development of batik indutry gives both positive and negative impacts on people life. One of the negative effects is the waste yielded from the production process which is potential to pollute the environment. The results of preliminary survey show that the COD examination of the sewage of “Batik Ayu” industry, which is located in Pijenan, Wijirejo, Pandak, Bantul, at the outlet was 570 mg/L, meaning that the waste still exceeding the threshold regulated by the Decree of Governor of DIY No. 7 in 2010. The purpose of this research was to know the effect ofelectrolysis time using aluminium electrodes on COD reduction of that industry waste, by conducting an experiment with pre-test post-test with control group design. The waste water sample for this study were obtained by using time combination method and with quota sampling technique. There were three electrolysis times used, i.e. 1 hour, 2 hour and 3 hour, which were measured in 10 replications. The results of data analysis with using one way anova from SPSSfor Windows at 0,05 level of signifcance, indicate that the COD reductions produced from the treatment groups and control group were not different. However, if compared individually, the COD reduction of each electrolysis time is higher than that of the control group.